Accurate identification of ALK positive lung carcinoma patients: novel FDA-cleared automated fluorescence in situ hybridization scanning system and ultrasensitive immunohistochemistry. - Esther Conde (Public Library of Science (PLoS), 2014)
Background Based on the excellent results of the clinical trials with ALK-inhibitors, the importance of accurately identifying ALK positive lung cancer has never been greater. However, there are increasing number of recent publications addressing discordances between FISH and IHC. The controversy is further fuelled by the different regulatory approvals. This situation prompted us to investigate two ALK IHC antibodies (using a novel ultrasensitive detection-amplification kit) and an automated ALK FISH scanning system (FDA-cleared) in a series of non-small cell lung cancer tumor samples. Methods Forty-seven ALK FISH-positive and 56 ALK FISH-negative NSCLC samples were studied. All specimens were screened for ALK expression by two IHC antibodies (clone 5A4 from Novocastra and clone D5F3 from Ventana) and for ALK rearrangement by FISH (Vysis ALK FISH break-apart kit), which was automatically captured and scored by using Bioview's automated scanning system. Results All positive cases with the IHC antibodies were FISH-positive. There was only one IHC-negative case with both antibodies which showed a FISH-positive result. The overall sensitivity and specificity of the IHC in comparison with FISH were 98% and 100%, respectively. Conclusions The specificity of these ultrasensitive IHC assays may obviate the need for FISH confirmation in positive IHC cases. However, the likelihood of false negative IHC results strengthens the case for FISH testing, at least in some situations.